(untitled) (Baghdad Science Journal, 2016)
A potentiostatic study of the behaviour of Inconel (600) in molar sulphuric acid has been carried out over the temperature range 293-313 K. Values have been established for the potentials and current densities of the corrosion, active-passive transition, passivity and transpassive states. For corrosion, the current density (ic) and potential (Ec) have been determined from well-defined Tafel lines. The potential and current density prior to the commencement of passivity have been obtained corresponding respectively to the critical potential (Ecr( and to the current density (icr) for the active-passive transition state. The passive range was defined by the respective potentials and current densities for passive film formation and dissolution. The dissolution point was correlated with transpassive potential (Et) and current density (it). All the estimated potentials and current densities for the various states were influenced by temperature and the presence of additives in the sulphuric acid. Additives such as nitric acid, thiourea and sodium chloride lowered the corrosion current density (ic) of the alloy while hydrochloric acid enhanced the value of ic. Addition of thiourea or sodium chloride or hydrochloric acid caused a shift in the corrosion potential (Ec) to less negative values while nitric acid shifted Ec to more negative potentials. The kinetic effect of the additives have been studies. Values of activation energy (E) were considered to be apparent and some negative values of E have been obtained with certain additives for the critical and passivity processes. Such negative E values were attributed to small values of true energies of activation together with relatively large exothermic enthalpies of such processes.